2006
DOI: 10.1038/oby.2006.112
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and Sex Variations in Overweight Self‐perception: Relationship to Sedentariness

Abstract: Ethnic and sex variations in overweight self-perception: relationship to sedentariness. Obesity. 2006;14:980 -988. Objective: With increasing frequency, health promotion messages advocating physical activity are claiming weight loss as a benefit. However, messages promoting physical activity as a weight loss strategy may have limited effectiveness and cross-cultural relevance. We recently found self-perceived overweight to be a more robust correlate of sedentary behavior than BMI in Los Angeles County adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 34 publications
5
38
2
Order By: Relevance
“…Moreover, Ghanaian and Surinamese participants in our study also referred to specific migration-related barriers to PA. Studies among immigrants in the United Kingdom and the United States, 22,39 have also noted that pressures associated with the 'immigrant condition' may thwart motivation for PA. In addition, corroborating findings from this study, the existence of cultural preferences for large body sizes, [40][41][42][43] and the barriers that such preferences represent for engaging in weight controlling activities, 44,45 have also been observed in other studies. According to a recent study in Ghana, however, body images are changing, particularly in the younger generation.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, Ghanaian and Surinamese participants in our study also referred to specific migration-related barriers to PA. Studies among immigrants in the United Kingdom and the United States, 22,39 have also noted that pressures associated with the 'immigrant condition' may thwart motivation for PA. In addition, corroborating findings from this study, the existence of cultural preferences for large body sizes, [40][41][42][43] and the barriers that such preferences represent for engaging in weight controlling activities, 44,45 have also been observed in other studies. According to a recent study in Ghana, however, body images are changing, particularly in the younger generation.…”
Section: Discussionsupporting
confidence: 77%
“…36 In contrast to our findings in active older women, studies of younger Latina women have reported body dissatisfaction to be present only if the woman was overweight or obese. [37][38][39] In our sample, waist circumference, but not BMI category or body weight, was an independent predictor of body image dissatisfaction only in the overweight and obese older women, and this did not vary with age. We did not observe associations between the distinct silhouettes and body mass index, regardless of weight category.…”
Section: ■ Discussionmentioning
confidence: 87%
“…Survey data suggest that African American women who are overweight are less likely than Hispanic or non-Hispanic white women to try to lose weight 313 and may not perceive themselves to be overweight. 368 Ethnic minority populations in general are underrepresented in the weight-control literature, although this may reflect the access (both location and eligibility requirements) of minority populations to the studies that have been conducted. Studies comparing weight loss in African Americans and whites in the same program indicate lower average weight loss among African Americans than whites, within sex.…”
Section: Children and Adolescents With Mental And Physical Disabilitiesmentioning
confidence: 99%